New species and records of the supertribe Stomatosematidi (Diptera: Cecidomyiidae) in Brazil - Carmo-Neto, Antonio Marcelino Do; Lamas, Carlos José Einicker; Urso-Guimarães, Maria Virginia (Zootaxa, 2019)
Six new species of the genus Stomatosema are described and illustrated: Stomatosema paratudo sp. nov., S. sisbiota sp. nov., S. terena sp. nov., S. pantaneirum sp. nov., S. terere sp. nov. and S. camilae sp. nov. These are the first records of Stomatosema for South America. The genus Didactylomyia is recorded for the first time in Brazil.